2011
DOI: 10.1097/igc.0b013e3182119d8d
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Sentinel Lymph Node Detection in Vulval Carcinoma: Is It Time for a Change in Clinical Practice?

Abstract: Sentinel lymph node detection is safe and accurate in assessing lymph node status in women with vulval cancer undergoing staging. The combined method using Tc-99m and methylene blue dye injection for SLN detection has the best detection rate. Routine ultrastaging of negative SLN improves the detection of nodal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Preoperative palpation of the groin [15] and other imaging modalities, such as PET/CT [8, 9] and MRI [10], have also shown to be inaccurate in the detection of inguinal lymph node metastases. Currently, the only technique that appear to be effective in the detection of lymph node metastases, is either the sentinel node procedure or inguinal femoral lymphadenectomy [16, 17]. The incidental finding on the CT scanning of a synchronous renal tumor and a cecal tumor with pulmonary metastases, contributed to earlier intervention and treatment of these malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative palpation of the groin [15] and other imaging modalities, such as PET/CT [8, 9] and MRI [10], have also shown to be inaccurate in the detection of inguinal lymph node metastases. Currently, the only technique that appear to be effective in the detection of lymph node metastases, is either the sentinel node procedure or inguinal femoral lymphadenectomy [16, 17]. The incidental finding on the CT scanning of a synchronous renal tumor and a cecal tumor with pulmonary metastases, contributed to earlier intervention and treatment of these malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol states that with bulky lymph nodes (92 cm), seen either on preoperative imaging or intraoperatively, SLN detection is unreliable and should not be used; other published data support this. 19,21 In one patient, the preoperative MRI reported bulky (92 cm) lymph nodes on the left side of the pelvis, suggestive of metastatic involvement. We performed SLN detection to identify SLN on the right side and removed bulky lymph nodes on the left to submit them for frozen section assessment.…”
Section: Sentinel Node Detectionmentioning
confidence: 99%
“…If no metastasis was identified in this initial section, then ultrastaging was performed according to the method as previously described. 20,21 According to TNM criteria, metastatic disease was classified as macrometastatic (92 mm), micrometastatic (0.2Y2 mm), or isolated tumor cells (ITCs; G0.2 mm). In all cases, a section of the primary cervical tumor was also immunostained with pan cytokeratin MNF-116 to confirm tumor cell positivity.…”
Section: Histopathologymentioning
confidence: 99%
“…During testing by Devaja et al, lymph nodes were detected by the double-mapping method in 98.3% of cases and accumulated vital dye in 93.3% cases (4). Our results have demonstrated that these methods are equivalent with blue dye having a small advantage (92.6% SLN found by double-mapping and 100% by accumulated vital blue dye).…”
Section: Discussionmentioning
confidence: 49%
“…However, 25 to 35% of patients with an early stage of vulvar carcinoma will have lymph node metastases. The publication of the results of the multicentre GROINSS-V study in 2008 and later examinations have shown that the sentinel lymph node biopsy method is reliable, the sensitivity is high and the 3-year survival rate of the patients is 97%, the incidence of early and late post-operative complications is 3-4 times less, and the groin recurrence rate does not reach 2.3% (3,4). According to Holschneider and co-authors, modern principles of vulvar carcinoma treatment include: individualisation of treatment; in case of monofocal tumours minimally invasive surgery is purposeful (5).…”
Section: Introductionmentioning
confidence: 99%